Marks of the transgenerational in some verses of “El libro devorado” - Matamala Pizarro, José (Revista Chilena de Literatura, 2020)
This article analyzes some verses contained in “El Libro devorado” by the poet Pablo Apellidos from Chillan. The book was given to the presbyter of Santo Domingo parish, as the foundation of his apostasy, to be later published in 2015 as a literary creation. The revision of the verses is contrasted with Sigmund Freud’s reflections regarding the role of the phylogenetic 2020transfer in the historical evolution of the individual. Within this transfer there are elements of a transgenerational cut delineating the adhesions of people to beliefs, ideals, and discomforts, among others. Religion is one of them, so in the book the poet Pablo seeks to release himself from the religious mark signed in his baptism and of Christianity as an Institution; to finally safeguard the teachings of Jesus and end up on the side of messianic hope.